Atrocity, Deviance, and Submarine Warfare : Norms and Practices during the World Wars - Ben-Yehuda, Nachman (Book collections on Project MUSE., 2013)
In an era of changing ethics, the submarine has inaugurated a new type of unrestricted naval warfare.